Algumas questões sobre autoritarismo e formação do ideário da arquitetura moderna carioca - Rocha, Ricardo (2006)
This work attempts to discuss the (apparent) contradictory relations among modern architecture and authoritarian State in Brazil. However, more than to notice the dangerous links between modernism and authoritarian politics, it is important to recognize the congenital authoritarian character in the formation of modern Brazil. In this sense, the main discussion is about the constitution of the "carioca" hegemony in the panorama of the Brazilian modern architecture, in an effort of comprehending its historical meaning as it is revealed in the analysis